K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

24 tháng 6 2019

A = 1/2 + 1/4 + 1/8 + ... + 1/128

A = 1/2^1 + 1/2^2 + 1/2^3 + ... + 1/2^7

2A = 1 + 1/2 + 1/2^2 + ... + 1/2^6

2A - A = 1 - 1/2^7 = A

24 tháng 6 2019

G = 5 - 5^2/1*6  5^2/6*11 - ... - 5^2/101*106

G = -5(-1 + 5/1*6 + 5/6*11 + ... + 5/101*106)

G = -5(-1 + 1 - 1/6 + 1/6 - 1/11 + ... + 1/101 - 1/106)

G = -1.(-1/106)

G = 1/106

5 tháng 4 2015

\(S=\frac{2^2}{\left(2-1\right)\left(2+1\right)}+\frac{3^2}{\left(3-1\right)\left(3+1\right)}+...+\frac{2008^2}{\left(2008-1\right)\left(2008+1\right)}\)

\(S=\frac{2^2}{2^2-1}+\frac{3^2}{3^2-1}+...+\frac{2008^2}{2008^2-1}=\frac{2^2-1+1}{2^2-1}+\frac{3^2-1+1}{3^2-1}+...+\frac{2008^2-1+1}{2008^2-1}\)

\(S=1+\frac{1}{1.3}+1+\frac{1}{2.4}+...+1+\frac{1}{2007.2009}=\left(1+1+...+1\right)+\left(\frac{1}{1.3}+\frac{1}{2.4}+...+\frac{1}{2007.2009}\right)\)Tính \(A=\frac{1}{1.3}+\frac{1}{2.4}+...+\frac{1}{2007.2009}=\frac{1}{2}.\left(\frac{2}{1.3}+\frac{2}{2.4}+...+\frac{2}{2007.2009}\right)\)

\(A=\frac{1}{2}.\left(1-\frac{1}{3}+\frac{1}{2}-\frac{1}{4}+\frac{1}{3}-\frac{1}{5}+...+\frac{1}{2007}-\frac{1}{2009}\right)=\frac{1}{2}.\left(\left(1+\frac{1}{2}+\frac{1}{3}+...+\frac{1}{2007}\right)-\left(\frac{1}{3}+\frac{1}{4}+...+\frac{1}{2009}\right)\right)\)

\(A=\frac{1}{2}.\left(1+\frac{1}{2}-\frac{1}{2008}-\frac{1}{2009}\right)=...\)

Vậy \(S=2007+A=...\)

 

10 tháng 9 2017

ngu như con lợn

ngu như con lợn

ngu như con lợn